Image Encryption Method Based on Image Dimension Transformation Using Chaotic Flow systems - J. Mansoor, Atheer; N. Abdullah, Hikmat; T. Zeboon, Hadi (Opción, 2019)
Image encryption today is divided into changing image pixels’ value or chang- ing image pixels’ coordinates. In this paper, an image encryption system based on changing both pixels’ value and position using one chaotic flow systems is proposed. At first, image dimension is changed form an M*N matrix into a vector of 1*(M*N), then Implement the random number generated from cha- os system to produce the final encrypted image. The system has been imple- mented on equal and non-equal dimension images and tested by using testing techniques:- correlation coefficient, DSF, ADC, PSNR, EQ ,ARE, MD, ID , measurement based on the value and position changing and entropy. Then the result is compared with the traditional scheme which uses ACM for scram- bling then any chaotic system for changing pixel’s value. The simulation results show that, keeping almost the same encryption results quality but with decreasing the required time for encryption and decryption.